The impact of growth promoters on muscle growth and the potential consequences for meat quality. (October 2016) - Parr, Tim; Mareko, Molebeledi H.D.; Ryan, Kevin J.P.; Hemmings, Krystal M.; Brown, David M.; Brameld, John M.
Abstract: To meet the demands of increased global meat consumption, animal production systems will have to become more efficient, or at least maintain the current efficiency utilizing feed ingredients that are not also used for human consumption. Use of growth promoters is a potential option for increasing production animal feed efficiency and increased muscle growth. The objective of this manuscript is to describe the mechanisms by which the growth promoters, beta-adrenergic agonists and growth hormone, mediate their effects, with specific consideration of the aspects which have implications for meat quality. Highlights: The impact of the growth promoters on muscle growth Impacts of fibre type and proteolysis on meat quality Effects of growth promoters on fibre type, proteolysis and metabolism